All-solid-state battery, preparation method thereof and electronic equipment

The pre-electrolyte layer was treated by the hot pressing method and combined with the solid-state electrolyte particle size setting, the solid-solid interface problem in all-solid-state batteries was solved, and the lithium ion diffusion efficiency and electrochemical performance were improved.

CN119905676APending Publication Date: 2025-04-29HUBEI YUNSEN TECHPARK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510135387.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The solid-solid interface problem in all-solid-state batteries leads to the long-distance diffusion of lithium ions, affecting the electrochemical performance.

Method used

When preparing an all-solid-state battery, the first pre-electrolyte layer and the second pre-electrolyte layer are processed by using the hot pressing method to form a solid electrolyte layer in one piece, and the bonding effect between the electrolyte layer and the positive electrode layer and the negative electrode layer is improved.

Benefits of technology

The interface combination effect between the solid electrolyte and the positive electrode layer and the negative electrode layer is improved, the lithium ion diffusion efficiency is improved, and the electrochemical performance of all solid state batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905676A_ABST
    Figure CN119905676A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of all-solid-state batteries, in particular to an all-solid-state battery, a preparation method of the all-solid-state battery and electronic equipment, and the preparation method of the all-solid-state battery, the preparation method of the all-solid-state battery comprises the following steps: preparing solid electrolyte slurry, the softening temperature of a binder in the solid electrolyte slurry being higher than the softening temperatures of a positive electrode layer binder and a negative electrode layer binder; coating a part of the solid electrolyte slurry on the positive electrode layer, and forming a first pre-electrolyte layer; coating the remaining part of the solid electrolyte slurry on the negative electrode layer, and molding to form a second pre-electrolyte layer; the first pre-electrolyte layer and the second pre-electrolyte layer are oppositely arranged in a butt joint mode, and then a hot-pressing method is adopted for processing to form a battery body; wherein the hot pressing temperature is used for promoting the softening of the binder in the solid electrolyte slurry and is lower than the softening temperature of the positive electrode layer binder and the negative electrode layer binder; and storing and sealing the battery body to form the all-solid-state battery. The all-solid-state battery has the effects of improving the solid-solid interface contact problem between the solid electrolyte and the positive electrode layer and between the solid electrolyte and the negative electrode layer, further improving the lithium ion long-distance diffusion problem for a thick pole piece, and comprehensively improving the performance of the all-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of all-solid-state batteries, and in particular to an all-solid-state battery and a preparation method thereof, and an electronic device. Background Art

[0002] Lithium-ion batteries mainly rely on liquid electrolytes. The flammable and volatile properties of liquid electrolytes lead to safety risks such as thermal runaway, fire, and explosion in the case of overheating, short circuit, overcharging, mechanical damage, etc. Using solid electrolytes to replace liquid electrolytes and develop all-solid lithium batteries can solve the safety hazards currently faced by liquid lithium-ion batteries and become the most promising next-generation lithium-ion battery follow-up technology. However, in liquid lithium-ion batteries, the flowing liquid electrolyte can fully infiltrate the electrode sheet and fill the pores of the electrode at the same time to form a good liquid-solid infiltration interface. However, the solid electrolyte in the solid-state battery cannot flow, which means that the solid-solid contact wetting effect of the solid electrolyte with the positive and negative electrodes is far inferior to the liquid-solid interface, and the effective contact area is far lower than the effective area of ​​the liquid electrolyte with the positive and negative electrodes. Solving the solid-solid interface problem in all-solid batteries and improving the electrochemical performance of solid-state batteries are current research hotspots.

[0003] In order to solve the solid-solid interface problem in all-solid-state batteries, one method is to use pressure to pressurize the electrode and the solid electrolyte layer so that the electrode and the solid electrolyte layer are in close contact with each other. However, when the applied pressure is too high, the battery element may be damaged or deformed; when the applied pressure is too low, sufficient adhesion between the electrode and the solid electrolyte layer cannot be ensured. Related document 1 discloses a method for manufacturing an all-solid-state battery, comprising: applying a slurry of a solid electrolyte layer to the surface of an electrode active material layer to form a patterned solid electrolyte layer, and pressurizing to form a solid electrolyte layer. This method brings the solid electrolyte layer and the electrode into sufficiently close contact with each other without deformation of the electrode shape or damage to the electrode.

[0004] Regarding the above-mentioned related technologies, there is a defect that the solid electrolyte layer is subjected to uneven force. Especially for thick electrodes (250-400 μm), the solid-solid interface problem further expands the long-distance diffusion problem of lithium ions. Summary of the invention

[0005] In order to improve the solid-solid interface contact problem between the solid electrolyte and the positive electrode layer and the negative electrode layer, and further improve the long-distance diffusion problem of lithium ions for thick electrodes, and comprehensively improve the performance of all-solid-state batteries, the purpose of this application is to provide an all-solid-state battery and its preparation method and electronic device.

[0006] In the first aspect, the preparation method of the all-solid-state battery provided in the present application adopts the following technical solution:

[0007] A method for preparing an all-solid-state battery comprises the following steps:

[0008] Prepare a solid electrolyte slurry, wherein the softening temperature of the binder in the solid electrolyte slurry is higher than the softening temperatures of the positive electrode layer binder and the negative electrode layer binder;

[0009] Applying a portion of the solid electrolyte slurry on the positive electrode layer and forming a first pre-electrolyte layer;

[0010] Applying the remaining solid electrolyte slurry on the negative electrode layer and forming a second pre-electrolyte layer;

[0011] The first pre-electrolyte layer and the second pre-electrolyte layer are arranged opposite to each other, and then subjected to a hot pressing process to form a battery body; wherein the hot pressing temperature in the hot pressing process is set to promote the softening of the binder in the solid electrolyte slurry and is lower than the softening temperature of the positive electrode layer binder and the negative electrode layer binder;

[0012] The battery body is housed and sealed to form an all-solid-state battery.

[0013] Optionally, preparing the positive electrode layer includes preparing a positive electrode slurry, applying the positive electrode slurry to a positive electrode current collector, and forming the positive electrode layer, wherein preparing the positive electrode slurry includes:

[0014] dispersing carbon black in octanol solvent to obtain a wet conductive agent;

[0015] The positive electrode active material, the positive electrode solid electrolyte, the impregnating conductive agent, the positive electrode layer binder and the positive electrode layer solvent are mixed and dispersed to obtain the positive electrode slurry, wherein the boiling point of the positive electrode layer solvent is lower than that of the octanol solvent.

[0016] Optionally, the mixing and dispersing of the positive electrode active material, the positive electrode solid electrolyte, the impregnating conductive agent, the positive electrode layer binder, and the positive electrode layer solvent comprises:

[0017] The positive electrode active material, the positive electrode solid electrolyte, the impregnating conductive agent, and the positive electrode layer binder are mixed and dispersed, and then the positive electrode layer solvent is added and continued to be mixed and dispersed to obtain the positive electrode slurry.

[0018] Optionally, the forming of the positive electrode layer comprises:

[0019] One-step molding, setting the molding temperature to be 20-30°C lower than the boiling point of the positive electrode layer solvent;

[0020] Secondary molding, set the molding temperature to 170-185℃.

[0021] Optionally, the positive electrode layer solvent is anisole.

[0022] Optionally, the positive electrode active material includes a small particle material with a median particle size of 6-8 μm and a large particle material with a median particle size of 10-12 μm, wherein the mass ratio of the small particle material to the large particle cobalt material is 1:2-3.

[0023] Optionally, the solid electrolyte slurry includes a solid electrolyte, and the median particle size of the solid electrolyte is 3-5 μm.

[0024] In the second aspect, the all-solid-state battery provided in this application adopts the following technical solution:

[0025] The all-solid-state battery is prepared using the above-mentioned all-solid-state battery preparation method.

[0026] In a third aspect, the electronic device provided by the present application adopts the following technical solution:

[0027] An electronic device comprises the all-solid-state battery and receives power supply from the all-solid-state battery.

[0028] In summary, the present application includes at least one of the following beneficial technical effects:

[0029] 1. Preform the solid electrolyte with the positive electrode layer and the negative electrode layer respectively, and then set the first pre-electrolyte layer and the second pre-electrolyte layer as a whole by overheating and pressing, so as to improve the interface bonding effect between the electrolyte layer / positive electrode layer and the electrolyte layer / negative electrode layer without affecting the bonding effect of the electrolyte layer; furthermore, the setting of the solid electrolyte particle size of the solid electrolyte layer can further improve the bonding effect between the electrolyte layer and the positive electrode layer and the negative electrode layer in the process of preforming with the positive electrode layer and the negative electrode layer and setting the electrolyte layer as a whole;

[0030] 2. The pretreatment of carbon black promotes the distribution of the conductive agent to take into account the effects of uniform dispersion and interconnection between the conductive agents, thereby improving the specific energy of the all-solid-state battery. Further combined with the positive electrode layer solvent setting and secondary molding, while reducing the porosity, it increases the permeability and the effect of electron path formation, thereby further improving the electrode conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a capacity-voltage cycle diagram of Example 2 of the present application;

[0032] Figure 2 It is the capacity-voltage cycle diagram of comparative example 1 of the present application. DETAILED DESCRIPTION

[0033] The present application is further described in detail below in conjunction with embodiments.

[0034] <All-solid-state battery>

[0035] The present application discloses an all-solid-state battery, comprising a packaging material, a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked in sequence in the packaging material. The preparation method of the all-solid-state battery comprises the following steps:

[0036] Step S1: preparing the positive electrode layer

[0037] S1.1, preparing positive electrode slurry, including:

[0038] S1.1.1, dispersing carbon black in octanol solvent to obtain a wet conductive agent;

[0039] In one embodiment, 0.5-1 weight part of carbon black is taken by weight, and the specific weight is determined according to the actual situation. Under stirring, octanol solvent is sprayed, and the amount of octanol solvent is sufficient to wet the surface of carbon black without liquid dripping. In one specific embodiment, 0.8 weight part of carbon black and 0.2 weight part of octanol solvent can be taken.

[0040] In this embodiment, carbon black is used as a conductive agent to collect current between the positive electrode active materials and between the positive electrode layer and the positive electrode current collector, and to provide a channel for electron transmission. The infiltration of octanol promotes the balanced dispersion and connection agglomeration of carbon black, that is, the zero-dimensional granular carbon black cooperates with the infiltration effect of octanol, which makes it easier for carbon black to be evenly dispersed on the surface of the active material particles and closely contact with the active material, and at the same time, enhances the conductivity of the bonding and interconnection between carbon black.

[0041] S1.1.2. The positive electrode active material, the positive electrode solid electrolyte, the wetting conductive agent, and the positive electrode layer binder are mixed and dispersed, and then the positive electrode layer solvent is added and continued to be mixed and dispersed to obtain a positive electrode slurry, wherein the boiling point of the positive electrode layer solvent is lower than that of the octanol solvent.

[0042] About positive electrode active materials:

[0043] In one embodiment, the positive electrode active material is 70-90 parts by weight, and the positive electrode active material is used to reversibly store and release lithium during the battery charging and discharging process. Exemplarily, the positive electrode active material can be lithium cobalt oxide (LiCoO2), nickel manganese cobalt LiNiMnCoO2 (NMC) and nickel cobalt aluminum LiNiCoAlO2 (NCA), lithium nickel oxide (LiNiO2), lithium manganese spinel (LiMn2O4), etc.; in one specific embodiment, the positive electrode active material can be selected from lithium cobalt oxide (LiCoO2), taking 80 parts by weight.

[0044] In order to improve the formation effect of carbon black conductive channel, in one embodiment, the positive electrode active material includes a small particle size material with a median particle size of 6-8μm and a large particle size material with a median particle size of 10-12μm, and the mass ratio of the small particle size material to the large particle size material is 1:2-3. Exemplarily, the mass ratio of the small particle size material to the large particle size material can be 1:2, 1:2.5, or 1:3, as long as the set quantity can achieve the effect of improving the formation effect of carbon black conductive channel. In one specific embodiment, taking lithium cobalt oxide (LiCoO2) as an example of the positive electrode active material, the small particle size material is lithium cobalt oxide with a median particle size of 6-8μm, and the large particle size material is lithium cobalt oxide with a median particle size of 10-12μm; further, the lithium cobalt oxide with a median particle size of 6-8μm can be taken as 22 parts by weight, and the lithium cobalt oxide with a median particle size of 10-12μm can be taken as 58 parts by weight.

[0045] About solid electrolyte for positive electrode:

[0046] In one embodiment, the positive electrode solid electrolyte takes 10-30 parts by weight, and the positive electrode solid electrolyte can be an oxide solid electrolyte, a sulfide solid electrolyte, etc. Exemplarily, the sulfide solid electrolyte can be a glassy and glass-ceramic electrolyte of the Li-PS system; in one specific embodiment, the solid electrolyte is a Li-PS glass-ceramic electrolyte, taking 20 parts by weight.

[0047] In one embodiment, the median particle size of the positive electrode solid electrolyte may be 3-5 μm.

[0048] About positive electrode layer binder:

[0049] In one embodiment, the positive electrode layer binder is 1-2 parts by weight, and can be polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC) or styrene butadiene rubber (SBR) or the like.

[0050] About the positive electrode layer solvent:

[0051] The boiling point of the positive electrode layer solvent is lower than that of the octanol solvent, and in order to improve the heating and forming effect, it is required to have a low vapor pressure. In one embodiment, the positive electrode layer solvent is selected as anisole.

[0052] S1.2, coating the positive electrode slurry on the positive electrode current collector

[0053] The positive electrode current collector can be used as a good conductor for electron movement. Specifically, it collects and outputs the current generated by the positive electrode active material and inputs the current to the positive electrode active material. Exemplarily, the positive electrode current collector is used to form a whole with the positive electrode layer composed of the positive electrode slurry, and can be copper, aluminum, iron-nickel alloy, carbon sheet, composite current collector, etc. In this embodiment, the positive electrode current collector is aluminum foil, and the thickness of the aluminum foil can be 10 to 16 μm. In this embodiment, the thickness of the aluminum foil can be 15 μm.

[0054] The positive electrode slurry is coated on the positive electrode current collector, and the coating thickness is set according to the set size of the all-solid-state battery. For example, it can be a thick electrode sheet, and the coating thickness can be 250-400 μm. In this embodiment, the coating thickness is 300 μm.

[0055] S1.3, forming a positive electrode layer by coating the positive electrode slurry on the positive electrode current collector, comprising:

[0056] S1.3.1. One-time molding. The molding method may be drying or drying combined with pressing. The molding temperature is set to be 20-30°C lower than the boiling point of the positive electrode layer solvent, and is adjusted specifically according to the drying conditions. For example, taking anisole as an example, the molding temperature may be set to 128°C. At this molding temperature, anisole is preferentially extracted in a relatively large amount, and the binder is simultaneously promoted to be initially molded.

[0057] S1.3.2. Secondary molding: the molding method may be drying, or drying combined with pressing. The molding temperature is set at 170-185°C, which is adjusted specifically according to the drying conditions. Within this molding temperature range, octanol is promoted to be extracted, and during the process of octanol extraction, anisole is further promoted to be completely extracted.

[0058] Step S2, coating a portion of the solid electrolyte slurry on the positive electrode layer and preliminarily forming a first pre-electrolyte layer, comprising:

[0059] Step S2.1, preparing a solid electrolyte slurry, wherein the solid electrolyte slurry includes a solid electrolyte, a binder, a solvent, and may also include additives such as an antioxidant or an anti-reducing agent.

[0060] In one embodiment, the solid electrolyte may be the same material as the positive electrode solid electrolyte in the positive electrode slurry;

[0061] In one embodiment, regarding the binder, it can be polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), etc. In this embodiment, polyvinylidene fluoride (PVDF) is selected. Besides being a binder, it also belongs to a lithium-ion conductive polymer material and has certain lithium-ion conductivity. Further, since it is specified that the softening temperature of the binder in the solid electrolyte slurry is higher than that of the binders in the positive electrode layer and the negative electrode layer, when the binder in the solid electrolyte slurry is selected as polyvinylidene fluoride (PVDF), the binders in the positive electrode layer and the negative electrode layer can be selected as polytetrafluoroethylene (PTFE).

[0062] In one embodiment, regarding the solvent, a non-polar solvent with low reactivity to the solid electrolyte is used.

[0063] During the preparation process, the solid electrolyte, binder, solvent, and other additives are mixed and dispersed evenly to obtain the solid electrolyte slurry.

[0064] Step S2.2: Coat a part of the solid electrolyte slurry on the positive electrode layer. In one embodiment, the amount of the part of the solid electrolyte slurry is such that it can be coated and formed on the positive electrode layer. Further, to improve the coating effect, a part of the solid electrolyte accounts for 40 - 60% of the mass of the solid electrolyte slurry. Preferably, it accounts for 50% of the mass of the solid electrolyte slurry.

[0065] Step S2.3: Initially form a first pre-electrolyte layer from the solid electrolyte slurry on the positive electrode layer. In one embodiment, the forming method can be drying, or drying combined with pressing. The forming temperature is set to be lower than the temperature at which the solvent in the solid electrolyte slurry evaporates and at the same time the binder in the solid electrolyte slurry is initially formed.

[0066] Step S3: Prepare the negative electrode layer

[0067] The negative electrode layer is not particularly limited as long as it can absorb and release lithium ions. Exemplarily, it can be a metallic lithium negative electrode, a silicon-based negative electrode, a carbon material negative electrode, an oxide negative electrode, etc. In one embodiment, taking the carbon material negative electrode as an example, it can be graphitized carbon, difficult-to-graphitize carbon, easily graphitized carbon, etc.; in another embodiment, taking the oxide negative electrode as an example, it can be an amorphous compound mainly composed of oxides such as SiOx (1 < x ≤ 2) and SOx (1 < x ≤ 2), lithium titanate (Li4Ti5O 12 )、TiO2, etc.

[0068] In one embodiment, the current collector for the negative electrode can be made of the same material as the current collector for the positive electrode. In this embodiment, the current collector for the negative electrode is a copper foil with a thickness of 6 - 12 μm.

[0069] Step S4, coating the remaining part of the solid electrolyte slurry on the negative electrode layer, and preliminarily forming a second pre-electrolyte layer, comprising:

[0070] Step S4.1, coating the remaining solid electrolyte slurry on the positive electrode layer;

[0071] Step S4.2, preliminarily shaping the solid electrolyte slurry on the positive electrode layer to form a second pre-electrolyte layer. In one embodiment, the shaping method can be drying, or drying combined with pressing, and the shaping temperature is set to be lower than the temperature required to disperse the solvent in the solid electrolyte slurry and preliminarily shape the binder in the solid electrolyte slurry.

[0072] Step S5, the first pre-electrolyte layer and the second pre-electrolyte layer are relatively butt-jointed and then hot-pressed to form a battery body; wherein the first pre-electrolyte layer and the second pre-electrolyte layer are integrated to form a solid electrolyte layer, and the hot-pressing temperature is used to soften the binder in the solid electrolyte slurry and is lower than the softening temperature of the positive electrode layer binder and the negative electrode layer binder.

[0073] In one embodiment, a pair of hot pressing molds can be set on both sides of the positive electrode current collector and the negative electrode current collector to clamp and then heat each hot pressing mold. Exemplarily, the temperature of the hot pressing mold can be set to 140°C, at which temperature the binder in the solid electrolyte slurry softens, prompting the fusion of the first pre-electrolyte layer and the second pre-electrolyte layer, and 140°C is lower than the softening temperature of the positive electrode layer binder and the negative electrode layer binder, and does not affect the existing structure of the positive electrode layer and the negative electrode layer. In addition, from the perspective of being able to firmly integrate each layer and inhibit the outflow of lithium ion conductive polymer materials, it is preferred that the pressure of a pair of hot pressing molds is 20MPa-50MPa.

[0074] In the above embodiment, during the working process: during charging, the lithium ions of the positive electrode layer diffuse to the particle surface, the positive electrode material is oxidized at the interface of the solid electrolyte / positive electrode layer, the lithium ions escape from the positive electrode and enter the solid electrolyte layer, and are transferred to the surface of the negative electrode layer particles through diffusion and migration in the solid electrolyte layer, and then embedded in the negative electrode layer particles through the electrochemical reaction at the interface of the solid electrolyte / negative electrode layer, and diffuse inward from the surface of the negative electrode layer particles; while the electrons migrate from the positive electrode side to the negative electrode through the external circuit. During discharge, the transmission of lithium ions and electrons is opposite.

[0075] <Electronic equipment>

[0076] The present application discloses an electronic device, which includes the above-mentioned all-solid-state battery.

[0077] The electronic device may be a printed circuit board with an all-solid-state battery installed. For example, the all-solid-state battery is installed on the printed circuit board through a welding process and is synchronously matched with a charging and discharging circuit setting. The electronic device may also be a portable mobile battery.

[0078] The above-mentioned electronic devices such as printed circuit boards and mobile batteries have all-solid-state batteries, so they can exert the effects of the above-mentioned all-solid-state batteries. In addition, the all-solid-state batteries of the present invention can also be applied to watches, hearing aids, sensor network terminals, portable game terminals, game controllers, real-time clock ICs, solar power generation, thermoelectric power generation, vibration power generation and other power storage elements.

[0079] Example 1

[0080] Embodiment 1 of the present application discloses an all-solid-state battery, comprising a packaging material, a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked in sequence and arranged in the packaging material. The preparation method of the all-solid-state battery comprises the following steps:

[0081] Step S1: preparing the positive electrode layer

[0082] S1.1, preparing positive electrode slurry, including:

[0083] The positive electrode active material, the positive electrode solid electrolyte, the conductive agent, and the positive electrode layer binder are mixed and dispersed, and then the positive electrode layer solvent is added and continued to be mixed and dispersed to obtain a positive electrode slurry;

[0084] Among them, the positive electrode active material is 80 parts by weight of lithium cobalt oxide with a median particle size of 10-12μm; the solid electrolyte for the positive electrode is a Li-PS glass ceramic electrolyte with a median particle size of 3-5μm, which is taken as 20 parts by weight; the conductive agent is 0.8 parts by weight of carbon black; the positive electrode layer binder is 1.5 parts by weight of polytetrafluoroethylene (PTFE); and the positive electrode layer solvent is selected as anisole.

[0085] S1.2. Apply the positive electrode slurry to a positive electrode current collector, wherein the positive electrode current collector is an aluminum foil with a thickness of 15 μm and a coating thickness of 300 μm.

[0086] S1.3, molding the positive electrode slurry coated on the positive electrode current collector to form a positive electrode layer, including: molding at a molding temperature of 128°C.

[0087] Step S2, apply half the volume of solid electrolyte slurry on the positive electrode layer, and preliminarily form a first pre-electrolyte layer, wherein the solid electrolyte slurry includes a solid electrolyte, a binder, and a solvent. Among them, the solid electrolyte is the same material as the solid electrolyte for the positive electrode in the positive electrode slurry; the binder is polyvinylidene fluoride (PVDF), and the solvent is anisole. During the preparation process, the solid electrolyte, the binder, and the solvent are mixed and evenly dispersed to obtain a solid electrolyte slurry.

[0088] Step S3, preparing a negative electrode layer, the negative electrode layer is an oxide negative electrode, and the current collector used for the negative electrode is a copper foil with a thickness of 10 μm.

[0089] Step S4: coating the remaining portion of the solid electrolyte slurry on the negative electrode layer and preliminarily shaping it to form a second pre-electrolyte layer.

[0090] Step S5: The first pre-electrolyte layer and the second pre-electrolyte layer are placed opposite to each other, and then hot-pressed at 140° C. and 25 MPa to form a battery body.

[0091] Step S6: accommodating and sealing the battery body to form an all-solid-state battery.

[0092] Example 2

[0093] Embodiment 2 of the present application discloses an all-solid-state battery, comprising a packaging material, a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked in sequence and arranged in the packaging material. The preparation method of the all-solid-state battery comprises the following steps:

[0094] Step S1: preparing the positive electrode layer

[0095] S1.1, preparing positive electrode slurry, including:

[0096] S1.1.1, take 0.8 parts by weight of carbon black, and disperse the carbon black in 0.2 parts by weight of octanol solvent to obtain a wet conductive agent;

[0097] S1.1.2, the positive electrode active material, the positive electrode solid electrolyte, the wetting conductive agent, and the positive electrode layer binder are mixed and dispersed, and then the positive electrode layer solvent is added and continued to be mixed and dispersed to obtain a positive electrode slurry;

[0098] The positive electrode active material is selected from 22 parts by weight of lithium cobalt oxide with a median particle size of 6-8 μm and 58 parts by weight of lithium cobalt oxide with a median particle size of 10-12 μm;

[0099] The solid electrolyte for the positive electrode is a Li-PS glass ceramic electrolyte with a median particle size of 3-5 μm, taking 20 parts by weight;

[0100] The positive electrode layer binder is 1.5 parts by weight of polytetrafluoroethylene (PTFE);

[0101] The positive electrode layer solvent is anisole.

[0102] S1.2. Apply the positive electrode slurry to a positive electrode current collector, wherein the positive electrode current collector is an aluminum foil with a thickness of 15 μm and a coating thickness of 300 μm.

[0103] S1.3, molding the positive electrode slurry coated on the positive electrode current collector to form a positive electrode layer, including: performing a primary molding at a molding temperature of 128° C., and then controlling the molding temperature to be 180° C. for a secondary molding.

[0104] Step S2, coating half the volume of the solid electrolyte slurry on the positive electrode layer, and preliminarily forming a first pre-electrolyte layer, comprising:

[0105] Step S2.1, preparing a solid electrolyte slurry, wherein the solid electrolyte slurry comprises a solid electrolyte, a binder, and a solvent.

[0106] The solid electrolyte is the same material as the positive electrode solid electrolyte in the positive electrode slurry; the binder is polyvinylidene fluoride (PVDF), and the solvent is anisole.

[0107] During the preparation process, the solid electrolyte, adhesive and solvent are mixed and evenly dispersed to obtain a solid electrolyte slurry.

[0108] Step S2.2: Apply half the volume of the solid electrolyte slurry on the positive electrode layer.

[0109] Step S2.3: Preliminarily shaping the solid electrolyte slurry on the positive electrode layer to form a first pre-electrolyte layer.

[0110] Step S3, preparing a negative electrode layer, the negative electrode layer is an oxide negative electrode, and the current collector used for the negative electrode is a copper foil with a thickness of 10 μm.

[0111] Step S4: coating the remaining portion of the solid electrolyte slurry on the negative electrode layer and preliminarily shaping it to form a second pre-electrolyte layer.

[0112] Step S5: The first pre-electrolyte layer and the second pre-electrolyte layer are placed opposite to each other, and then hot-pressed at 140° C. and 25 MPa to form a battery body.

[0113] Step S6: accommodating and sealing the battery body to form an all-solid-state battery.

[0114] Comparative Example 1

[0115] Comparative Example 1 of the present application discloses an all-solid-state battery, comprising a packaging material, a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked in sequence in the packaging material. The preparation method of the all-solid-state battery comprises the following steps:

[0116] Step S1, preparing a positive electrode layer, same as in Example 1;

[0117] Step S2, coating the solid electrolyte slurry on the positive electrode layer and shaping it to form an electrolyte layer, wherein the preparation of the solid electrolyte slurry is the same as that of Example 1.

[0118] Step S3, preparing a negative electrode layer, the negative electrode layer is an oxide negative electrode, and the current collector used for the negative electrode is a copper foil with a thickness of 10 μm.

[0119] Step S4: The electrolyte layer and the negative electrode layer are placed opposite to each other, and then hot-pressed at 140° C. and 25 MPa to form a battery body.

[0120] Step S6: accommodating and sealing the battery body to form an all-solid-state battery.

[0121] test

[0122] The all-solid-state positive electrodes obtained in Examples 1-2 and Comparative Example 1 were subjected to charge and discharge tests, specifically:

[0123] Using a battery charge and discharge test system, the test temperature is 60°C, and the specific capacity, initial efficiency, cycle capacity retention rate, etc. of the all-solid-state lithium battery are characterized at a rate of 0.1C. The unit of specific capacity is mAh / g, which reflects the amount of electrical energy that can be stored per unit mass of battery material; cycle capacity retention rate = discharge capacity of the current cycle / initial capacity × 100%.

[0124] The test results are shown in Table 1 below:

[0125] Table 1

[0126] Specific capacity Cycle capacity retention rate (300 cycles) Cycle capacity retention rate (800 cycles) Example 1 224.76 91.05% 83.3% Example 2 235.49 92.49% 85.3% Comparative Example 1 216.83 80.4% 66.7%

[0127] According to the above table, the specific capacity of Example 2 is better than that of Example 1. The reason is that the pretreatment of carbon black promotes the distribution of the conductive agent to take into account the effects of uniform dispersion and interconnection between the conductive agents, thereby improving the specific energy of the all-solid-state battery. This effect can be further reflected by the cycle capacity retention rate test.

[0128] Furthermore, the positive electrode active material includes materials with different median particle size ranges, which causes the positive electrode active material to present a multi-peak distribution, reduces the probability of increased porosity due to particle incompatibility, and further increases the specific capacity.

[0129] Then combined with secondary molding, the porosity is reduced while the permeability is increased, the effect of forming an electronic path is increased, and the conductivity of the electrode is further improved.

[0130] According to the above table and attached Figure 1-2It can be seen that the cycle capacity retention rates of Example 1 and Example 2 are better than those of Comparative Example 1. The reason is that the solid electrolyte is preformed with the positive electrode layer and the negative electrode layer respectively, and then the first pre-electrolyte layer and the second pre-electrolyte layer are integrated together with the overheating and pressing, which improves the interface bonding effect between the electrolyte layer / positive electrode layer and the electrolyte layer / negative electrode layer without affecting the bonding effect of the electrolyte layer; furthermore, the setting of the solid electrolyte particle size of the solid electrolyte layer can further improve the bonding effect of the electrolyte layer with the positive electrode layer and the negative electrode layer in the process of preforming with the positive electrode layer and the negative electrode layer and the integrated setting of the electrolyte layer;

[0131] Furthermore, after 300 cycles of charge and discharge, the maximum difference in cycle capacity retention between the embodiment and the comparative example is 12.09%, while after 800 cycles, the maximum difference in cycle capacity retention between the embodiment and the comparative example is 18.6%, which further illustrates the improvement of the interface bonding effect by this method, and can be further verified by the specific capacity data.

[0132] The above describes the all-solid-state battery and its preparation method and electronic device of the present invention according to the embodiments, but the present invention is not limited thereto, and the structure of each part can be replaced with any structure having the same function. In addition, any other structure can be added to the present invention.

[0133] The embodiments of this specific implementation are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. The same components are represented by the same figure marks. Therefore, any equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing an all-solid-state battery, characterized in that: The following steps are involved: Prepare a solid electrolyte slurry, wherein the softening temperature of the binder in the solid electrolyte slurry is higher than the softening temperatures of the positive electrode layer binder and the negative electrode layer binder; Applying a portion of the solid electrolyte slurry on the positive electrode layer and forming a first pre-electrolyte layer; Applying the remaining solid electrolyte slurry on the negative electrode layer and forming a second pre-electrolyte layer; The first pre-electrolyte layer and the second pre-electrolyte layer are arranged opposite to each other, and then subjected to a hot pressing process to form a battery body; wherein the hot pressing temperature in the hot pressing process is set to promote the softening of the binder in the solid electrolyte slurry and is lower than the softening temperature of the positive electrode layer binder and the negative electrode layer binder; The battery body is housed and sealed to form an all-solid-state battery.

2. The method for preparing an all-solid-state battery according to claim 1, characterized in that: The preparation of the positive electrode layer includes preparing a positive electrode slurry, applying the positive electrode slurry to a positive electrode current collector and forming the positive electrode layer, wherein the preparation of the positive electrode slurry includes: dispersing carbon black in octanol solvent to obtain a wet conductive agent; The positive electrode active material, the positive electrode solid electrolyte, the impregnating conductive agent, the positive electrode layer binder and the positive electrode layer solvent are mixed and dispersed to obtain the positive electrode slurry, wherein the boiling point of the positive electrode layer solvent is lower than that of the octanol solvent.

3. The method for preparing an all-solid-state battery according to claim 2, characterized in that: The method of mixing and dispersing the positive electrode active material, the positive electrode solid electrolyte, the impregnating conductive agent, the positive electrode layer binder, and the positive electrode layer solvent comprises: The positive electrode active material, the positive electrode solid electrolyte, the impregnating conductive agent, and the positive electrode layer binder are mixed and dispersed, and then the positive electrode layer solvent is added and continued to be mixed and dispersed to obtain the positive electrode slurry.

4. The method for preparing an all-solid-state battery according to claim 2, characterized in that: The forming of the positive electrode layer comprises: One-step molding, setting the molding temperature to be 20-30°C lower than the boiling point of the positive electrode layer solvent; Secondary molding, set the molding temperature to 170-185℃.

5. The method for preparing an all-solid-state battery according to claim 4, characterized in that: The positive electrode layer solvent is anisole.

6. The method for preparing an all-solid-state battery according to claim 2, characterized in that: The positive electrode active material comprises a small particle material with a median particle size of 6-8 μm and a large particle material with a median particle size of 10-12 μm, wherein the mass ratio of the small particle material to the large particle cobalt material is 1:2-3.

7. The method for preparing an all-solid-state battery according to claim 6, characterized in that: The solid electrolyte slurry comprises a solid electrolyte, and the median particle size of the solid electrolyte is 3-5 μm.

8. All-solid-state battery, characterized in that: The all-solid-state battery is prepared by the preparation method of any one of claims 1 to 7.

9. An electronic device, characterized in that It includes the all-solid-state battery as claimed in claim 8 and receives power supply from the all-solid-state battery.